SISTEM PENYARADAN PADA EKSPLOITASI HUTAN PINUS DI JAWA TENGAH - S Sutopo; Maman M Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
A paper mill is to be erected in Cilacap, Central Java in the near future. The raw material must come from the hilly pine forests in the Pekalongan and Banyumas area. The mill's daily intake ranges between 1,000-1,500 m3 of relatively small diameter pine logs. Therefore manual yarding system must be improved to increase its productivity. One way to do this is to yard with a wheeled cariage.The purpose of this investigation is to determine the feasibility of this yarding system in hilly pine forest terrain. The investigation reveals the following :Yarding system by Roda II is favourable in the hilly pine forest area in Central Java.This system increases the income per manday approximately by 31% compared to the traditional system (ngglebeg) for a distance of 1,0 km, and 18% for a distance of 2.0 km.Yarding productivity by Roda II is approximately 1.58 m3 per day.